Uso de beta – glucanos como potenciador de crecimiento en lechones (Sus scrofa domesticus) en el Ecuador” - Toaza Junco, Irina Carolina (2023)
Every day producers are looking for improvements in pig feeding, to achieve higher performance and lower costs in obtaining raw materials. The appropriate techniques and tools are not always available to guarantee effectiveness in terms of nutrition. For this, the objective of this work was to determine the use of beta-glucans as a growth enhancer in piglets in Ecuador. Regarding the methodology of this non-experimental research work, of a bibliographic nature, it was carried out with the compilation of prior and scientific information from authors oriented on the subject. The use of this fiber is an increasingly relevant practice in the pork industry. Beta-glucans are natural polysaccharides present in certain feed ingredients, such as yeast and some cereals, which have demonstrated significant benefits in the health and efficient growth of piglets in recent decades. Based on the results obtained, it is essential to understand that these compounds stimulate the immune system, improve nutrient absorption and promote intestinal health in piglets, which contributes to better performance in pig farming. It is concluded that the use of beta-glucans as growth enhancers in piglets can be an effective strategy to improve the productivity and health of animals, in turn minimizing production expenses and generating greater economic income for pig farmers.